Preliminary results on the effects of orthopedic implant stiffness fixed to the cut end of the femur on the stress at the stump-prosthetic interface - Ismail Boudjemaa; A. Sahli; A. Benkhettou; S. Benbarek (Fracture and Structural Integrity)
A lot of trans-femoral amputation patients experience skin breakdown due to the pressures and shear stresses in the stump-prosthesis interface. In this study, a finite element model was employed to investigate the stresses at the stump interface in the case of an orthopedic implant fixed to the cut end of the femur. By changing the stiffness of this implant, we aim to see how the stiffness of this implant affects the stresses in the interface between the amputated limb and the prosthesis. To find out the effects of implant stiffness, five values for the elastic modulus, ranging from 0.1 to 0.5 Mpa, with an interval of 0.1 Mpa were employed in the implant structure of the FE model.